1994
DOI: 10.1007/bf00195911
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of repeated administration of atenolol and captopril in healthy volunteers

Abstract: The central effects of atenolol (50 mg tds) and captopril (50 mg tds) ingested for a period of seven days were studied in ten healthy volunteers. A placebo and two active control drugs, methyldopa (250 mg tds) and oxazepam (10 mg), were included in the design. Oxazepam was ingested on the seventh day only, with a placebo being taken on the preceding six days. On the seventh day, central effects of the drugs were tested at 10.00-11.00 h (session 1), immediately before the subjects' last dose of each drug and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Previous studies in patients with hypertension have suggested that ACE inhibitors may have beneficial effects on cognitive function while other cardiac medications may be detrimental. [34][35][36] Further studies are merited to determine whether treatment with ACE inhibitors results in significant change in cognitive function in older people. The impact of ACE inhibitors on morbidity, including cognitive function, in elderly patients with normal systolic function is being evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in patients with hypertension have suggested that ACE inhibitors may have beneficial effects on cognitive function while other cardiac medications may be detrimental. [34][35][36] Further studies are merited to determine whether treatment with ACE inhibitors results in significant change in cognitive function in older people. The impact of ACE inhibitors on morbidity, including cognitive function, in elderly patients with normal systolic function is being evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a controlled study of psychiatrically normal, hypertensive patients, however, we have shown that the treatment of the hypertension with ACE inhibitors was associated with only a small, statistically nonsignificant, reduction in scores on a depression scale [Braszko et al, 2003]. Furthermore, in healthy volunteers, captopril is reported to have no effect on depressive mood scores [Currie et al, 1990;McDevitt et al, 1994]. These results, however, should perhaps not be surprising in light of the knowledge that clinically proven antidepressants have mood-elevating effects in depressed individuals only; they have no significant effect in nondepressed populations.…”
Section: Angiotensin and Antidepressant Activitymentioning
confidence: 93%
“…Hypertensive patients were seen to have significantly greater anxiety scores than normotensive controls, but these elevated scores were reduced after therapy with ACE inhibitors [Braszko et al, 2003]. In normotensive, psychiatrically normal subjects, antihypertensive doses of ACE inhibitors have no effect on mood scores [Currie et al, 1990;McDevitt et al, 1994]. Similarly antihypertensive doses of the AT 1 receptor antagonist Losartan have been shown to have no effect on anxiety scores in healthy volunteers [Nicholson et al, 2001].…”
Section: Angiotensin and Anxiolytic Activitymentioning
confidence: 96%
“…The ACEi and ARBs are both reported to have potential nootropic effects (that is, they may alter, improve, or augment cognitive performance) in various learning and memory paradigms. General effects of single doses of captopril were shown to improve short‐term memory (Currie et al, 1990), while another study showed no effects of a similar dose on subjectively assessed alertness or mood (McDevitt et al, 1994). The decrease in endogenous Ang II in the brain seems to improve cognitive performance by enhancing cGMP pathways, although only captopril, not other ACEis, is effective in enhancing the memory, suggesting it to be because of other putative unknown mechanisms (Raghavendra et al, 2001).…”
Section: The Physiological Roles and Therapeutic Potential Of Ace And...mentioning
confidence: 99%